Achievements and Challenges of Classical Swine Fever Eradication in Brazil - de Oliveira, Luís Guilherme [UNESP]; Gatto, Igor Renan Honorato; Mechler-Dreibi, Marina Lopes [UNESP]; Almeida, Henrique M S [UNESP]; Sonálio, Karina [UNESP]; Storino, Gabriel Yuri [UNESP] (MDPI, 2020)
Classical swine fever virus (CSFV) causes one of the most critical diseases in the porcine industry worldwide. In Brazil, the first description of the infection was reported in 1888, and the national recognition of the first free zone (FZ) occurred in 2001. Brazil has been recently recognized (2015-2016) by the World Organisation for Animal Health (OIE) with an FZ involving 15 states and the Federal District, corresponding to 95% of the industrial production of pigs in the country, and a non-free zone (NFZ), comprised by the North and Northeast regions of the country, with approximately 18% of the national pig herd and 5% of industrial production. This review aims to describe the history, the control and eradication actions, the recent occurrence of outbreaks in the NFZ, and the results obtained by the surveillance systems' action in the FZ for CSF in Brazil since its creation. In the passive surveillance system, the notification of the suspect cases of classical swine fever (CSF) is mandatory while in the active surveillance system adopted in the FZ consists of serological monitoring of certified swine breeding farms (CSBFs), intensive pig farming (IPF), non-technified pig herds (NTPig), surveillance in slaughterhouses and monitoring the populations of wild pigs. In this region, the last outbreaks of the disease occurred in 1998, while in the NFZ, 28 outbreaks were detected from 2005 to 2017, with an apparent lethality rate of 93.96% (840/894). However, in 2018 and 2019, 68 new outbreaks were registered with an apparent lethality rate of 75.05% (1095/1459). Therefore, in 2019, the Brazil CSF-Free Strategic Plan was created to eradicate the infection from the country's NFZ, since outbreaks in this region present a risk of reintroducing the disease FZ. Finally, differences in characteristics between the regions show factors that still need to be considered for the construction of a robust surveillance system in the NFZ and some improvements in the FZ. Thus, the control of CSF throughout the Brazilian territory requires strict sanitary guidelines, promoting animal health and, consequently, the national production chain's competitiveness.
Keywords: classical swine fever infection; domestic pigs; outbreaks; South America; wild boars